Delivering on the promise of early childhood education for black children: An equity strategy. Issue 183 (12th September 2022) - Iruka, Iheoma U.
Abstract: The early years are a critical period for setting children up for school and life. For Black children who are exposed to adversities before and after birth, early childhood education (ECE) has been shown as one potentially strategy to mitigate against systemic inequities. However, evidence continues to show the negative impact of structural racism and system inequities in the lives of Black children. While Black children continue to thrive even in the face of biased experiences and unfairness, it is imperative that simultaneous attention focus on how to best support the well‐being Black children and address systemic racism. This paper discusses ECE and its evidence and calls for policies and strategies that dismantle racism inherent in ECE by ensuring equitable funding, equity‐centered monitoring, and equity‐centered assessment of family engagement. To support Black children's health, development, and well‐being, we must attend to policies that address equitable access, supports, experiences, and outcomes.